QI Olympics: A Game-Based Educational Activity in Quality Improvement - Elizabeth Hanson; Glenn Rosenbluth; Katie McPeak (Association of American Medical Colleges, 2013)
Abstract This resource is a game-based team educational activity designed to teach the fundamentals of quality improvement in a fun and efficient way. In this activity, we provide brief instruction on the Plan-Do-Study-Act model for improvement. This is followed by a series of team-building games tailored to reinforce quality improvement concepts and to allow the learners to practice their quality improvement skills in a safe environment. Although the principles relate directly to clinical quality improvement, the activity itself is non-clinical and is therefore suitable for learners across a wide range of disciplines and levels of training. This resource contains our introductory didactic materials as well as instructions and worksheets for three quality improvement activities. We have also included debriefing prompts to guide your discussion with the learners in this activity. Target learners are those with minimal quality improvement experience or those wishing to refresh or practice their quality improvement skills. Thirty-eight residents participated in this resource. For each game, the teams completed three-to-four Plan-Do-Study-Act cycles and documented their changes and outcomes on worksheets. Of the 38 residents who participated, 32 completed the postactivity written survey (84%). Thirty-one of the 32 (97%) who completed the survey rated the activity as excellent or very good in "overall quality," "clear goals and objectives," "attainment of goals and objectives," and "applicability to residency and the practice of medicine."